The Purpose and Objectives of Financial and Management Accounting in Determining the Structure of Supply Costs in Grain Producing Clusters (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The article examines the necessity and features of organizing financial and management accounting in grain clusters.